2011
DOI: 10.1021/es104362g
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Degradation of Perfluoro-2-methyl-3-pentanone: Photolysis, Hydrolysis and Hydration

Abstract: Perfluorinated carboxylic acids are widely distributed in the environment, including remote regions, but their sources are not well understood. Perfluoropropionic acid (PFPrA, CF(3)CF(2)C(O)OH) has been observed in rainwater but the observed amounts can not be explained by currently known degradation pathways. Smog chamber studies were performed to assess the potential of photolysis of perfluoro-2-methyl-3-pentanone (PFMP, CF(3)CF(2)C(O)CF(CF(3))(2)), a commonly used fire-fighting fluid, to contribute to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 30 publications
2
47
1
Order By: Relevance
“…The maximum absorbance was found at 306 nm with s max = (6.38 AE 0.32) Â 10 À20 cm 2 molecule À1 , in good agreement with those reported in previous studies. 4,5 In Fig. 4,5 In Fig.…”
Section: Uv-vis Absorption Cross Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum absorbance was found at 306 nm with s max = (6.38 AE 0.32) Â 10 À20 cm 2 molecule À1 , in good agreement with those reported in previous studies. 4,5 In Fig. 4,5 In Fig.…”
Section: Uv-vis Absorption Cross Sectionsmentioning
confidence: 99%
“…5 Previous studies have shown that PFMP reactions with OH and Cl atoms are very slow. Furthermore, this procedure may be extended to other terrestrial locations through calculation of the average actinic radiation at the corresponding latitudes, as described for PFMP.…”
Section: C(o)ch 3 (Circle) and Cf 3 C(o)ch 2 Ch 3 (Triangle) (B) Cf mentioning
confidence: 99%
“…The effect of UV radiation on the properties of EFA and EP composite material containing EFA are analyzed. It is known (13) that NovecTM1230 decomposes under the influence of UV. Samples of pure EFA and EP composite containing EFA were kept at the average UV radiation value (5000 MJ/m 2 ) from 1 to 50 hours at 25 ℃.…”
Section: Climate Tests Of Fire Extinguishing Composite Materials Contamentioning
confidence: 99%
“…Perfluoro (2-methyl-3-pentanone) (FK-5-1-12, 3M TM Novec TM 1230) is one of the most promising agents (11) . It is aligned with the Montreal Protocol and is a liquid under normal conditions (12,13) .…”
mentioning
confidence: 99%
“…As with other compounds that contain no halogen other than fluorine, the ozone depletion potential (ODP) is zero. In addition, we determined that the atmospheric degradation of fluoroketones do not lead to the generation of long chain acids that are of environmental concern [6]. For liquid fluoroketone, care must be taken to prevent its discharge into water.…”
Section: Environmental Impactmentioning
confidence: 99%